Sondheim! the Birthday Concert ; a celebration of one of Broadway's greatest legends - Sondheim, Stephen 1930-2021 (Ellen M. Krass Productions, 2010)
This concert is a collection of some of Stephen Sondheim's most popular songs in celebration of his birthday